Buscopan labeled with carbon‐14 and deuterium. (17th October 2016) - Latli, Bachir; Stiasni, Michael; Hrapchak, Matt; Li, Zhibin; Grinberg, Nelu; Lee, Heewon; Busacca, Carl A.; Senanayake, Chris H.
Abstract : Hyosine butyl bromide, the active ingredient in Buscopan, is an anticholinergic and antimuscarinic drug used to treat pain and discomfort caused by abdominal cramps. A straightforward synthesis of carbon‐14– and deuterium‐labeled Buscopan was developed using scopolamine, n ‐butyl‐1‐ 14 C bromide, and n ‐butyl‐ 2 H 9 bromide, respectively. In a second carbon‐14 synthesis, the radioactive carbon was incorporated in the tropic acid moiety to follow its metabolism. Herein, we describe the detailed preparations of carbon‐14– and deuterium‐labeled Buscopan. Abstract : A straightforward synthesis of carbon‐14 and deuterium‐labeled Buscopan was developed using scopolamine, n ‐butyl‐1‐ 14 C bromide, and n ‐butyl‐ 2 H 9 bromide, respectively. In a second carbon‐14 synthesis, the radioactive carbon was incorporated in the tropic acid moiety. The detailed preparations of carbon‐14 and deuterium‐labeled Buscopan are reported.